Prion protein deficiency impairs hematopoietic stem cell determination and sensitizes myeloid progenitors to irradiation - Capucine Siberchicot; Nathalie Gault; Nathalie Déchamps; Vilma Barroca; Adriano Aguzzi; Paul-Henri Roméo; J. Pablo Radicella; Anne Bravard; Jacqueline Bernardino-Sgherri (Haematologica, 2020)
Highly conserved among species and expressed in various types of cells, numerous roles have been attributed to the cellular prion protein (PrPC). In hematopoiesis, PrPC regulates hematopoietic stem cell self-renewal but the mechanisms involved in this regulation are unknown. Here we show that PrPC regulates hematopoietic stem cell number during aging and their determination towards myeloid progenitors. Furthermore, PrPC protects myeloid progenitors against the cytotoxic effects of total body irradiation. This radioprotective effect was associated with increased cellular prion mRNA level and with stimulation of the DNA repair activity of the Apurinic/pyrimidinic endonuclease 1, a key enzyme of the base excision repair pathway. Altogether, these results show a previously unappreciated role of PrPC in adult hematopoiesis, and indicate that PrPC-mediated stimulation of BER activity might protect hematopoietic progenitors from the cytotoxic effects of total body irradiation.